Children with Speech Language and Communication Needs in England: Challenges for Practice - Dockrell, Julie Elizabeth; Howell, Peter; Leung, Diane; Fugard, Andrew J. B. (Frontiers in Education, 2017)
Teachers and Speech and Language Therapists (SLTs) share concern about children’s Speech Language and Communication Needs (SLCNs) but they have different foci because of their professional roles. Contemporary research has identified the challenges to schools when meeting the needs of children with SLCN, highlighted terminological controversies and has increased opportunities for professional development. The views of 170 Educationalists and SLT professionals in England about SLCN, and the children’s associated needs were compared for similarities and differences in an on-line survey that employed both categorical responses and Likert scales. Comparisons were made between Teacher and SLT groups and between SLTs working in schools and clinics. There were few significant differences between the views of SLTs in clinics and education. By contrast there were often large and significant differences between teachers and SLTs. Education professionals were less familiar with terminology related to speech difficulties, did not discriminate between behaviours that might differentiate speech from language difficulties and varied in the ratings given about other associated difficulties. Additionally, education professionals showed awareness of academic and behaviour difficulties associated with language difficulties and highlighted associated problems with reading and writing. SLTs felt confident in their understanding of the relevant terminology but there was less clarity in the features that discriminated speech from language difficulties. Both the Educationalists and SLTs valued additional training needs with over 50% of the Education staff reporting that they had no training in SLCN. The lack of clarity about the language markers of SLCN by teachers and the requests for tools to help in the identification of speech and language problems in school-age children are important areas to address. Both SLTs and Education staff emphasised the co-occurrence of difficulties with reading comprehension and written text production, highlighting the importance of profiling children’s language learning needs rather than a reliance on diagnostic categories.